Experiences of Online Group-Counseling Based-Video Conference on High School Students in Indonesia - I Putu Agus Apriliana (Jurnal Bimbingan dan Konseling Indonesia, 2023)
Counseling methods with integrated information and communication technology in schools are interesting to discuss. Recently the conditions of the COVID-19 Pandemic have made all educational activities in schools online, and in Indonesia. We predict the use of information and communication technology in high school students to be easier to implement. Because they are more familiar with information and communication technology than students at the primary school level. This qualitative study aims to describe the experiences of students in secondary schools receiving online counseling. The semi-structured interviewed involved eight students, both chat messages and video call session by WhatsApp application. Participant of study are students has experience attending online group counseling via video conferencing. Data on the benefits of online group counseling, experiences in cyberspace, and barriers were analyzed thematically. The findings in this study explain that online group counseling has provided a solution, and some students feel it is precious to help. Their insight and self-help increase on the issues discussed. It was so convenient for them that some students expressed relationship school counselor with students-client. Network problems and smartphone overheating are obstacles. The implications of the results of this study as a reference for improving the implementation of online counseling.